Fostering the Development of Young Students’ Analytical Thinking by use of a Problem-solving Method - Lanting, Lavinia Suvi (Journal of research in science, mathematics and technology education, 2025)
The analytical thinking level of secondary school students in the Netherlands has been on the decline for the past few years, with grave consequences for the mathematical level of these students, who often struggle later on in their academic careers. In particular, these students showcase underdeveloped basic skills such as critical reading and critical thinking, vital to many subjects in secondary school. Problem-solving methods have been utilised widely across the literature to foster both academic skills and the performance of students. In this research, a problem-solving method, inspired by Polya’s four step method, is introduced and extended to include a reflection part (inside phase) to help students foster and develop their analytical thinking. Qualitative findings from a study conducted with K–8 students are reported and discussed to determine the degree to which the methodology helped these students develop their analytical thinking compared to a parallel class of K–8 students.